(untitled) (CIPEEX, 2025)
Introduction: Swimming involves multiple factors to enhance athletic performance, among which respiratory control stands out. Spirometry tests have become increasingly important to monitor the respiratory system. Objective: To analyze cardiopulmonary respiratory capacities in high-performance swimmers using spirometry devices.Methodology: The study included 24 high-performance swimmers, divided into an experimental group and a control group, with respiratory assessment performed using spirometry. Partial Results: Data collected included sex, age, height, weight, BMI, FVC (Forced Vital Capacity), %FVC (Percentage of FVC), FEV1 (Forced Expiratory Volume in the first second), FET (Forced Expiratory Time), and FEV1/FVC ratio. Conclusion: Additional data collection is necessary to obtain long-term results.